The effects of peroperative fluid administration on postoperative acid-base and electrolyte balance in patients undergoing total gastrectomy - (:unkn) unknown (My University, 2014)
Objective: This prospective clinical study aimed to compare acid-base and electrolyte balance in patients who were administered perioperative normal saline (group NS) or Ringer's Lactate (Group RL) infusion for total gastrectomy surgery. Method: Fifty patients scheduled to have total gastrectomy surgery for gastric cancer were recruited in the study. We performed arterial blood gas analysis after induction, at 1st, 12th and 24th postoperative hours, and recorded data regarding patients' metabolic conditions with sodium, chloride and potassium levels. Results: The mean pH values of Group RL and NS showed a significant decrease at the 1st postoperative hour, then an increase in the 6th, 12th and 24th hours. The arterial PaCO2, PaO2, and oxygen saturation values did not show any significant difference in both groups at all times. Serum sodium levels were significantly lower in RL Group during all postoperative period. There was not a significant difference in serum potassium levels. Serum chloride levels at postoperative 6th, 12th and 24th hours were significantly lower in RL Group than NS Group. While Chloride level decreased significantly at the 6th hour in Group NS, compared to the end of the surgery, it did not change significantly at 24th hour. Conclusion: Regarding the metabolic condition, in normal saline group, hyperchloraemic metabolic acidosis was obtained at first postoperative hour as a temporary side effect. Besides, we have observed a tendency for hyponatremia in Ringer's Lactate group. We are in the opinion that normal saline infusion can be confidently used in major abdominal surgeries.
Keywords: Crystalloid; Gastrectomy; Normal saline; Ringer's Lactate